Holding the shop together: German industrial relations in the postwar era - Silvia, Stephen J. (Ithaca, NY., 2013)
"Since the onset of the Great Recession, Germany’s economy has been praised for its superior performance, which has been reminiscent of the “economic miracle” of the 1950s and 1960s. Such acclaim is surprising because Germany’s economic institutions were widely dismissed as faulty just a decade ago. In Holding the Shop Together, Stephen J. Silvia examines the oscillations of the German economy across the entire postwar period through one of its most important components: the industrial relations system.